2023
DOI: 10.3390/healthcare11030399
|View full text |Cite
|
Sign up to set email alerts
|

“I Assumed It Would Be Somebody Who Had a Stroke That Was Doing This”: Views of Stroke Survivors, Caregivers, and Health Professionals on Tailoring a Relaxation and Mindfulness Intervention

Abstract: Stroke survivors and informal caregivers experience high levels of stress and anxiety, linked to heightened risk of secondary stroke in survivors. Relaxation and mindfulness could reduce stress and anxiety; being most effective when tailored to the target populations. Aims of the PPI include to: (1) consult on possible alterations to an existing relaxation and mindfulness intervention, delivered via YouTube/DVD and (2) discuss relevance and preference of prompts and cues designed to facilitate the daily practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Over time aphasiologists have suggested various strategies and techniques to promote the inclusion of PWA in research teams [ 8 ]. Indeed, their inclusion in stroke rehabilitation studies has increased as evidenced in allied health research: physiotherapy [ 9 ], occupational therapy [ 10 , 11 ], psychology [ 12 ] and multidisciplinary research [ 13 ]. Unfortunately, research so far involving PWA as research partners has revealed their involvement as tokenistic and nonmeaningful [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over time aphasiologists have suggested various strategies and techniques to promote the inclusion of PWA in research teams [ 8 ]. Indeed, their inclusion in stroke rehabilitation studies has increased as evidenced in allied health research: physiotherapy [ 9 ], occupational therapy [ 10 , 11 ], psychology [ 12 ] and multidisciplinary research [ 13 ]. Unfortunately, research so far involving PWA as research partners has revealed their involvement as tokenistic and nonmeaningful [ 8 ].…”
Section: Introductionmentioning
confidence: 99%